2019
DOI: 10.1038/s41413-018-0038-3
|View full text |Cite
|
Sign up to set email alerts
|

NOTUM inhibition increases endocortical bone formation and bone strength

Abstract: The disability, mortality and costs caused by non-vertebral osteoporotic fractures are enormous. Existing osteoporosis therapies are highly effective at reducing vertebral but not non-vertebral fractures. Cortical bone is a major determinant of non-vertebral bone strength. To identify novel osteoporosis drug targets, we phenotyped cortical bone of 3 366 viable mouse strains with global knockouts of druggable genes. Cortical bone thickness was substantially elevated in Notum−/− mice. NOTUM is a secreted WNT lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 55 publications
(73 reference statements)
5
60
0
Order By: Relevance
“…4a). They include the Wnt-regulator notum (Notum), which regulates bone formation [46][47][48] and a distintegrin and metalloproteinase like member (Adamtsl2), which is implicated in geleophysic dysplasia 49 . The majority of osteocyte transcriptome signature genes (78%, n=968) had not previously been shown to have a role in the skeleton ('unannotated' in Fig.…”
Section: A Unique Transcriptome Signature Defines the Osteocytementioning
confidence: 99%
“…4a). They include the Wnt-regulator notum (Notum), which regulates bone formation [46][47][48] and a distintegrin and metalloproteinase like member (Adamtsl2), which is implicated in geleophysic dysplasia 49 . The majority of osteocyte transcriptome signature genes (78%, n=968) had not previously been shown to have a role in the skeleton ('unannotated' in Fig.…”
Section: A Unique Transcriptome Signature Defines the Osteocytementioning
confidence: 99%
“…Their research with 1 has shown that Notum is a potential drug target for stimulating bone formation and treating osteoporosis [7]. However, although 1 demonstrates low plasma clearance, the structure contains an essential carboxylic acid and acids tend to have low passive brain penetration [8][9][10][11][12].…”
Section: Lp-922056 (1)mentioning
confidence: 99%
“…Pharmacokinetic (PK) data for 1 was generated in vivo in mouse to evaluate brain penetration (Table 1; Figure 1) (see Supporting Information Tables S1-S3 (File 1)). The route of administration and dose were selected to most closely match relevant published mouse disease model studies [5,7]. Following single oral dose (p.o.)…”
Section: Improved Synthesis Ofmentioning
confidence: 99%
“…Wnt ligands are post‐translationally modified by a palmitoleate moiety attached to a serine, while the recently discovered Wnt deacylase Notum can remove this moiety and acts as a secreted feedback antagonist . Notum belongs to the α/β‐hydrolase superfamily of enzymes, and its structure reveals a large hydrophobic pocket at the active site, suggesting its enzyme activity can be blocked by small molecule inhibitors, and inhibition of Notum can increase bone density and may have the potential to rejuvenate stem cells …”
Section: Introductionmentioning
confidence: 99%
“…We recently reported the development of 2‐phenoxyacetamides as Notum inhibitors . One of the biggest limitations of these inhibitors is their inability or limited ability to cross the blood‐brain barrier, even though they are found to be effective in vitro . In order to identify new chemically divergent small molecules and generate structural information for rational design of new inhibitors, we used a crystallography‐based fragment screening approach .…”
Section: Introductionmentioning
confidence: 99%